PENGARUH ROA, QR, DER, DAN GROWTH TERHADAP DIVIDEN POLICY PADA PERUSAHAAN MANUFAKTUR - Putra, Bryan Johannes; Trisnawati, Estralita; Indrajati, MF Djeny (Jurnal Paradigma Akuntansi, 2025)
An investor will certainly expect a profit from his investment, the profit will be distributed in the form of dividends. Many things affect the dividend distribution policy. This study aims to see how the influence of profitability, liquidity, leverage, and company growth on dividend policy in manufacturing companies listed on the IDX for the 2018-2020 period. The purposive sampling method is a method of selecting samples that will be carried out in this study, with 114 total samples of manufacturing companies used from 2018-2020. The data processed in this study used eviews 10 and microsoft excel 2019 and was processed using a panel data regression model. The results in this study indicate that profitability and leverage have a positive and significant effect on dividend policy, while liquidity has an insignificant negative effect on dividend policy, and company growth has a significant and negative effect on dividend policy.